Sensibilidad y especificidad de cuatro técnicas de diagnóstico radiográfico en lesiones periapicales, 2013”. estudio in vitro - Neyra Panta, Claudia Fiorella (2014)
Sensitivity and Specificity of four Diagnostic Radiographic Techniques Periapical lesions, is a study that was conducted on specimens of human skulls, in order to apply different radiographic techniques for the detection of periapical lesions in diagnostic upper first molar teeth. This prospective, cross-sectional comparative and observational study aimed to compare the sensitivity and specificity of four diagnostic radiographic techniques, such as conventional periapical radiography, applying the technique of the bisector and Parallelism, Digital Panoramic X-ray and CT Cone beam for detection of periapical lesions. The study sample consisted of 88 pieces specifically upper molar tooth belonging to 44 specimens of human skulls; the total sample only the cavity was performed to simulate periapical lesions in 60% of the total, while the remaining 40% remained intact on these samples diagnostic differences were noted and found radiographic signs were typed. The results showed the sensitivity and specificity of periapical radiographic method using the technique of bisecting was S = 88.46%, E = 100%, PPV = 100%, NPV = 72.5%, while the parallel technique S = 17% E = 100%, PPV = 100%, NPV = 44.3%, with the panoramic digital technique a sensitivity of S = 88.7%, E = 88.6%, PPV = 92.2%, NPV of 83.8% was obtained; while the cone beam CT scan sensitivity was S = 98.1%, E = 94.3%, PPV = 96.3%, NPV = 97.1%. Concluded that the most sensitive method for the diagnosis of periapical lesions after the computed tomography technique was the digital panoramic technique, on the other hand both the bisector technique as the technique of parallel are highly specific. In terms of positive predictive values in the case, were similar for all techniques, with respect to the negative predictive values panoramic digital technique had higher negative predictive value after the cone beam computed tomography.